Enhancing Teacher Retention and Compensation through Effective Principal Leadership and Professional Competence in Islamic Private Elementary Schools - Lusy Listiawaty; Sri Utaminingsih; Nuryati Djihadah (CV. Edujavare Publishing, 2026)
Education is a key pillar of national development, and teachers play a central role in ensuring the success and quality of learning. This study aims to analyze the influence of principal leadership and teacher professional competence on teacher retention, with compensation as a mediating variable. This study employed a quantitative approach, using a survey to collect data from teachers in a private Islamic school. Path analysis was used to examine the direct and indirect relationships between the variables. The findings indicate that principal leadership and teacher professional competence positively influence teacher retention, both directly and through compensation as a mediating factor. These results reinforce the importance of school leaders' role in managing compensation and professional development as a sustainable retention strategy. This study highlights how compensation can act as a bridge between leadership and retention, and how professional competence reinforces this dynamic. In conclusion, retaining great teachers requires more than just a salary. It demands visionary leadership, meaningful professional development, and a workplace culture that values ​​the contributions of every educator. By focusing on these areas, schools can build strong and loyal teams that drive long-term success and educational excellence.